PERSAINGAN PENDIDIKAN TINGGI ANTARNEGARA DI INDONESIA DALAM PENGATURAN GENERAL AGREEMENTS IN TRADE IN SERVICES - Supriyanto, Agustinus (Jurnal Cakrawala Pendidikan, 2016)
The concept of liberalization of education in the General Agreements in Trade in Services (GATS) of the World Trade Organization (WTO) contains four medes of supply for all members: first, that of a cross border supply, meaning that the educayional liberalization takes place from the territory of one member into tha of any other member, second, the one implying that the educational liberaliqation is conducted through the commercial presence of one member in the territory of any other member, third, that of consumer movement, meaning that the educational liberalization happens in the territory of one member in the form of service to consumers from any other member, and fourth, that of personnel movement, meaning that the educational liberalization is conducted through the presence of natural persons of a member in the territory of any other member.